GABAergic and pyramidal neurons of deep cortical layers directly receive and differently integrate callosal input. - Karayannis, T; Huerta-Ocampo, I; Capogna, M (2007)
We studied the involvement of deep cortical layer neurons in processing callosal information in the rat. We observed with electron microscopy that both parvalbumin (PV)-labeled profiles and unlabeled dendritic spines of deep cortical layer neurons receive synapses from the contralateral hemisphere. Stimulation of callosal fibers elicited monosynaptic excitatory postsynaptic currents in both layer VI pyramidal neurons and gamma-aminobutyric acidergic (GABAergic) interneurons immunopositive for the vesicular GABA transporter and PV. Pyramidal cells had intrinsic electrophysiological properties and synaptic responses with slow kinetics and a robust N-metyhl-D-aspartate (NMDA) component. In contrast, GABAergic interneurons had intrinsic membrane properties and synaptic responses with faster kinetics and a less pronounced NMDA component. Consistent with these results, the temporal integration of callosal input was effective over a significantly longer time window in pyramidal neurons compared with GABAergic interneurons. Interestingly, callosal stimulation did not evoke feedforward inhibition in all GABAergic interneurons and in the majority of pyramidal neurons tested. Furthermore, retrogradely labeled layer VI pyramidal neurons of the contralateral cortex responded monosynaptically to callosal stimulation, suggesting interconnectivity between callosally projecting neurons. The data show that pyramidal neurons and GABAergic interneurons of deep cortical layers receive interhemispheric information directly and have properties supporting their distinct roles.